Enhanced Na+-substituted Li2Mg2Mo3O12 ceramic substrate based on ultra-low temperature co-fired ceramic technology for microwave and terahertz polarization-selective functions. Issue 2 (February 2023) - Li, Fuyu; Li, Yuanxun; Li, Yilei; Feng, Xin; Zhang, Jinping; Liu, Xinyan; Lu, Yongcheng; Wang, Shengye; Liao, Yulong; Tang, Tingting; Wen, Qiye
Abstract: A novel Li2 Mg2- x Na2 x Mo3 O12 ( x = 0.09) ceramic with ultra-low sintering temperature is prepared by the solid-state reaction method. This ceramic (625 °C) exhibits excellent microwave dielectric properties ( ε r = 7.9, Q× f = 43844 GHz, τ f = −48.3 ppm/°C), terahertz transmission properties ( ε r 1 = 7.4, tan σ 1 = 0.0158, Tcoefficient = 0.598), and chemical compatibility with Ag. For the first time, two polarization selective devices are designed in the microwave and terahertz regions by using this ceramic substrate, respectively. The transmission amplitudes of the right- and left-handed circularly polarized waves of the microwave device at 9.7 GHz are 0.895 and 0.019, respectively. The transmission coefficients of the y - and x -polarized waves of the terahertz device at 0.45 THz are 0.598 and 0.075, respectively. Both functions are verified by the overall far-field radiation pattern. This work promotes the application of dielectric ceramics and ULTCC technology in the microwave and terahertz regions.